PERAN ANGGARAN PRODUKSI DALAM MENGENDALIKAN BIAYA DAN MENJAGA KELANCARAN PROSES OPERASIONAL PERUSAHAAN - Wa Ode Jeslin; Try Wahyuni Mawatdah; Khoirotunnisa Limbong; Dini Vientiany (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the role of the production budget in controlling production costs and maintaining the smoothness of a company’s operational processes. The production budget is a crucial component of management planning and control, as it serves as a guideline for allocating resources and managing production activities efficiently. This research uses a qualitative approach with a library research method by reviewing relevant textbooks, scientific journals, and research articles related to production budgeting. The results indicate that the production budget functions as a tool for planning, organizing, supervising, and controlling production activities. Through an effective production budget, companies are able to control raw material costs, direct labor costs, and manufacturing overhead costs by analyzing variances between budgeted and actual costs. Proper and realistic production budgeting helps minimize cost inefficiencies, reduce waste, and ensure continuous and efficient operational performance, thereby supporting the achievement of organizational objectives in a competitive business environment.